Smart utopia VS smart reality: Learning by experience from 10 smart city cases. (March 2017) - Anthopoulos, Leonidas
Abstract: 20 years after the appearance of literature evidence and the launch of the first, pioneering cases, the smart city domain remains ambiguous and generates an increasing argument with regard to its feasibility and potential. Indeed, today the smart city domain is being characterized by an emerging market that provides novel solutions for cyber-physical integration in the urban space; a competitive standardization arena that attempts to clarify the domain and homogenize these solutions; a growing network of city alliances, forums and market places that aim to bring together scientists, practitioners and city governments in an attempt to define a common urban future; and a promising international network of scholars that studies and evolves the domain. Nevertheless, a "common understanding" of what smart city is or could be missing and generates questions regarding whether a "smart utopia" - that is the outcome of the "wedding" of vendors and local governments - drives the above efforts and leaves out real community problems. The aim of this paper is to perform an analysis of 10 representative international city cases that claim to be smart. The analysis is based on a multi-method that combines literature evidence, official websites and reports, narrative city walks, and interviews with corresponding officials. The outcomes distinguish utopia from reality, introduce a pool of evidence that can justify whether a city can claim to be smart and depict a brief view of the future smart city. Highlights: Questions existing smart city environment with regard to a "smart utopia" figure Explores 10 smart city cases with a multi-methods approach Compares theoretical findings from the 10 cases with practical evidence Defines a set of primary features that a case must obtain in order to "self-claim" that it concerns a smart city Depicts the future smart city according to the examined cases' plans